Factors affecting death in COVID-19 patients with neurological disease manifestations - Okparasta, Andika; Azwinda, Eka (International Journal of Research in Medical Sciences, 2022)
Background: Coronavirus disease-2019 (COVID-19) can also attack the nervous system besides the respiratory system. It is recorded that 25% of all COVID-19 cases are accompanied by neurological disorders with a higher death rate. The study aimed to determine the neurological manifestations of COVID-19 and analyse the factors that contribute to death in COVID-19 with neurological disorders. Methods: This was an analytical cross-sectional study that included 183 patients with COVID-19 and neurological disorders at the Department of Neurology Dr. Mohammad Hoesin Central General Hospital, Palembang, Indonesia from March 2020 to June 2021. We evaluated the risk factor for mortality in COVID-19 patients with neurological disorders. Results: In this study, 78.1% of patients were under 65 years old, and 89% were male with hypertension (51.4%) as the most comorbid disease. A total of 66.1% of the study subjects had peripheral leukocytes 10,000/mm3, with 82% having an NLR value of 3.3. The mortality rate of COVID-19 patients with neurological disorders is 30.1%. Neurological manifestations recorded were CVD (71.3%), encephalitis meningitis, seizures, exacerbation of myasthenia gravis, GBS, and myelitis. The bivariate analysis found no risk factors associated with death in COVID-19 patients with neurological disorders. Multivariate regression analysis obtained that male sex and diabetes mellitus have a correlation with death in COVID-19 accompanied by neurological disorders. Conclusions: Male COVID-19 patients with neurological manifestations and diabetes mellitus have a higher risk for death.